2019
DOI: 10.1021/acsomega.9b01079
|View full text |Cite
|
Sign up to set email alerts
|

Designing SnO2 Nanostructure-Based Sensors with Tailored Selectivity toward Propanol and Ethanol Vapors

Abstract: The application of metal oxide-based sensors for the detection of volatile organic compounds is restricted because of their high operating temperatures and poor gas sensing selectivity. Driven by this fact, we report the low operating temperature and high performance of C 3 H 7 OH and C 2 H 5 OH sensors. The sensors comprising SnO 2 hollow spheres, nanoparticles, nanorods, and fishbones with tunab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 58 publications
4
25
0
Order By: Relevance
“…Both LT- and LTP-SnO 2 films exhibited two peaks at binding energies of 487.3 and 495.7 eV corresponding to Sn 3d 5/2 and Sn 3d 3/2 , as previously reported. 31 The single peak at 487.3 eV is assigned to the Sn 4+ oxidation state of SnO 2 . However, there is no visible peak at the binding energy of 485.8 eV that corresponds to the Sn 2+ oxidation state which indicates the formation of SnO.…”
Section: Resultsmentioning
confidence: 99%
“…Both LT- and LTP-SnO 2 films exhibited two peaks at binding energies of 487.3 and 495.7 eV corresponding to Sn 3d 5/2 and Sn 3d 3/2 , as previously reported. 31 The single peak at 487.3 eV is assigned to the Sn 4+ oxidation state of SnO 2 . However, there is no visible peak at the binding energy of 485.8 eV that corresponds to the Sn 2+ oxidation state which indicates the formation of SnO.…”
Section: Resultsmentioning
confidence: 99%
“…• defects is morphology-dependent and supporting the idea to exploit the controlled generation of these defects not only for boosting the electrical response but also the selectivity of the sensors [44].…”
mentioning
confidence: 78%
“…45 It has also been reported that the Sn 4+ and Sn 2+ peaks have symmetric shapes. [51][52][53][54] In the top graph of Fig. 6b, the raw data of the Sn 3d 5/2 peak with background subtracted are shown together with two symmetric fitted curves of Sn 4+ and Sn 2+ ; however, the overall fitted curve in red does not fit the raw data well.…”
Section: Xps Studies Of the Snte (111) (001) And (211) Samplesmentioning
confidence: 99%